2015
DOI: 10.22146/jp.8561
|View full text |Cite
|
Sign up to set email alerts
|

Pengambilan Keputusan Penggunaan Alat Kontrasepsi Istri Dalam Keluarga

Abstract: Salah satu kunci kesuksesan keluarga berencana adalah partisipasi para istri dan suami dalam pemakaian kontrasepsi. Penggunaan kontrasepsi selama ini masih didominasi oleh istri. Pembuatan keputusan dalam pemakaian kontrasepsi oleh istri dipengaruhi oleh beberapa faktor. Tingkat pengetahuan dan pengalaman pemakaian kontrasepsi akan mempengaruhi pembuatan keputusan. Banyak istri tidak mengetahui jenis kontrasepsi yang terbaik buat dirinya dan bagaimana kelebihan dan kekurangan dari masing-masing metode kontrase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…According to this study, health professionals' experience various husbands' roles in women's health. Previous Indonesian's study had assessed husbands' roles in several specific areas, for example, husbands' support during breastfeeding (Pratami, 2016), family planning (Kusmindari et al, 2016;Setiadi, 2015), and cancer screening (Aggraeni, 2016;Arkiang, 2016;Marlina, 2015). Not only in Indonesia, but studies with focus on husbands' support were also conducted in several Muslim dominated countries: Egypt and Jordan (Hamdan-Mansour et al, 2016;Ohashi et al, 2014;Taha et al, 2013).…”
Section: Massive Roles Of Muslim Husbands In Women's Healthmentioning
confidence: 99%
“…According to this study, health professionals' experience various husbands' roles in women's health. Previous Indonesian's study had assessed husbands' roles in several specific areas, for example, husbands' support during breastfeeding (Pratami, 2016), family planning (Kusmindari et al, 2016;Setiadi, 2015), and cancer screening (Aggraeni, 2016;Arkiang, 2016;Marlina, 2015). Not only in Indonesia, but studies with focus on husbands' support were also conducted in several Muslim dominated countries: Egypt and Jordan (Hamdan-Mansour et al, 2016;Ohashi et al, 2014;Taha et al, 2013).…”
Section: Massive Roles Of Muslim Husbands In Women's Healthmentioning
confidence: 99%
“…Berdasarkan indeks otonomi pengambilan keputusan perempuan pada Tabel 2 tingkat kekuatan pengambilan keputusan perempuan tertinggi dalam penggunaan kontrasepsi adalah pada perempuan dalam usia 35-39 tahun atau sekitar 64,63%. Hasil ini lebih tinggi dari penelitian lain di Indonesia dimana penentu pengambilan keputusan dalam masalah keluarga cukup kuat di 53,09% dan diputuskan bersama suami sebesar 58,48% (Setiadi & Iswanto, 2015). Sedangkan yang dilakukan di Pakistan yaitu 33%, namun masih lebih rendah untuk usia di atas 39 tahun (Nadeem et al, 2021).…”
Section: Pembahasanunclassified
“…MKJP sering diangap masyarakat sebagai alat kontrasepsi dengan efek samping yang berbahaya sehingga menjadi pemicu masyarakat untuk memilih alat kontrasepsi jangka pendek (Manurung, 2013;Picavet, Van der Leest, & Wijsen, 2011) Seiring meningkatnya pengetahuan, partisipasi kerja dan pemberdayaan pada perempuan membuka peluang bagi perempuan untuk mempunyai otonomi dalam pengambilan keputusan. Hal ini berimplikasi pada meningkatnya Spenggunaan kontrasepsi pada perempuan (Setiadi & Iswanto, 2015;Yaya, Uthman, Ekholuenetale, & Bishwajit, 2018). Penelitian lain menyebutkan perempuan yang menggunakan kontrasepsi cenderung memiliki keberdayaan dalam rumah tangga terutama dalam pengambilan keputusam rumah tangga sehari-hari (Fathurrahman, 2016;Setiadi & Iswanto, 2015).…”
Section: Pembahasanunclassified
“…Studies in Indonesia found that factors which influence women's participation in cancer screening were familymainly husbandeconomic factors, accessibility to health services, the roles of health providers, social culture, and women's motivation (Aqni, 2013;Hasbiah, 2004;Marlina, 2013;Ningrum, 2012;Nurhasanah, 2008;Ompusungu, 2012;Rahma, 2012;Tresnawati, 2012;Wahyuni, 2011;Wijayanti, 2011;Yuliwati, 2012). Several studies assessed husbands' involvement in perinatal periods, family planning, and cancer (Anggraeni & Benedikta, 2016;Arkiang, 2016;Kim et al, 2012;Kusmindari, Zinaida, Pasmawati, & Saputra., 2016;Marlina, 2015;Musyriqoh, 2013;Pratami, 2016;Setiadi, 2015). However, no study has focused on Muslim husbands' views of their role as the majority of studies applied a quantitative approach.…”
Section: List Of Figuresmentioning
confidence: 99%
“…In Indonesia, several studies have been conducted into men's participation in women's health, including husbands' support during breastfeeding (Pratami, 2016), family planning (Kusmindari, Zinaida, Pasmawati, & Saputra., 2016;Setiadi, 2015), and cancer screening (Aggraeni, 2016;Arkiang, 2016;Kim et al, 2012;Marlina, 2015;Musyriqoh, 2013). None of these studies included Muslim husbands in the sample criteria, three used a qualitative approach, and only two studies were published in English, the rest were in the Bahasa Indonesia language.…”
Section: Search Strategymentioning
confidence: 99%